The Core Marketing Concept: The Foundation of a Consumer-Oriented Business Strategy - Eka Safitri; Enrico Jonathan Hartono; Lalu Fatria Zulhadi; Lia Qelina; Lucia Anindya Wijayakusuma (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This research is motivated by the demands of global competition in the healthcare sector, which places consumers at the center of business strategy, where the success of hospitals is determined not only by the quality of medical services but also by their ability to respond dynamically to patient needs. The purpose of this study is to examine theories and previous research on the core marketing concept and to explore the role of consumer orientation as the foundation of a sustainable business strategy. The method used is qualitative research with a literature study design through an in-depth review of books, scientific journals, and relevant literature selected purposively based on theme, credibility, and currency. The findings indicate that the core marketing concept significantly contributes to understanding consumer needs, wants, and demands, while also driving innovation, loyalty, and organizational competitiveness. The integration of consumer orientation into business strategies has been proven to foster sustainability, as it links organizational goal achievement with added value for consumers. The implications of this research emphasize that the application of the core marketing concept is not only theoretically relevant but also practical as a foundation for formulating business strategies that are responsive to market changes and oriented toward long-term competitive advantage.